1964
DOI: 10.1128/jb.87.5.1060-1066.1964
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Heparin on Herpes Simplex Virus

Abstract: Inhibitory effect of heparin on herpes simplex virus. J. Bacteriol. 87:1060-1066. 1964.-A substance inhibitory to herpes simplex virus was observed during experiments with leukocyte cultures. The component in the cultures responsible for this inhibition was identified as heparin. The minimal inhibitory concentration required to inhibit 30 to 300 TCD5 of the virus in human amnion tissue 1060

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
3

Year Published

1971
1971
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(78 citation statements)
references
References 20 publications
0
75
0
3
Order By: Relevance
“…This has already been proposed for the treatment of both hepatitis C (He et al, 2015) and Ebola virus (Sakurai et al, 2015) infections. Heparin, the widely used anticoagulant, has potentially attractive features including activity against attachment and entry of the enveloped viruses, human simplex (HSV) (Herold et al, 1996;Nahmias and Kibrick, 1964), human immunodeficiency (HIV) (Baba et al, 1988), SARS coronavirus (Vicenzi et al, 2004), and influenza (H5N1) . Here, we explore the effects of heparin on ZIKV infection in human neural progenitor cells (hNPCs) with particular regard to virus replication and induction of cytopathic effects (CPE) resulting in cell death.…”
Section: Introductionmentioning
confidence: 99%
“…This has already been proposed for the treatment of both hepatitis C (He et al, 2015) and Ebola virus (Sakurai et al, 2015) infections. Heparin, the widely used anticoagulant, has potentially attractive features including activity against attachment and entry of the enveloped viruses, human simplex (HSV) (Herold et al, 1996;Nahmias and Kibrick, 1964), human immunodeficiency (HIV) (Baba et al, 1988), SARS coronavirus (Vicenzi et al, 2004), and influenza (H5N1) . Here, we explore the effects of heparin on ZIKV infection in human neural progenitor cells (hNPCs) with particular regard to virus replication and induction of cytopathic effects (CPE) resulting in cell death.…”
Section: Introductionmentioning
confidence: 99%
“…43 Heparan sulfate has been shown to block the initial phase of HSV infection. 57,58 More recent investigations revealed that glycoproteins from the HSV-1 and HSV-2 viruses are known to interact directly with 3-O-sulfated heparin, which is abundantly expressed on host cells. 54,[59][60][61][62][63] These studies suggest that the binding of heparan sulfate to gD prevents its interactions with host cell receptors.…”
Section: Influenza Virusmentioning
confidence: 99%
“…The broad antiviral activity of UTIb is shown in Table 1. Heparin, which may be used medically to prevent clotting, has narrow antiviral activity but deserves to be mentioned because of its potent activity against HIV-1 (Nahmias and Kibrick, 1964;Baba et al, 1988;Rider, 1997). Below we will consider the properties of the constitutive broadly active inhibitors, i.e.…”
Section: Serum: Innate Inhibitorsmentioning
confidence: 99%